Pengaruh Pendekatan Saintifik dalam Proses Belajar Mengajar Siswa Kelas VIII Materi Lingkaran - Maryani, Maryani; Effendi, Herlina; Sabantaro, Henky (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to determine students' learning outcomes who are taught using the scientific approach method in groups and not in groups. This research is quantitative. The study population was grade VIII students of SMP Negeri 03 Bengkulu City. In this study, sampling was carried out by purposive sampling because not all samples have criteria that match the phenomenon under study. The two classes chosen were Class VIII A and VIII B, each of which contained eight students. Each student gets material based on the same curriculum, the two samples in the same class, the teacher uses the same method, the characteristics of learning, and the students' initial abilities. Collecting data used in this study using observation and test questions. Based on the results of the above data using the non-parametric Mann Whitney Test, it was found that the results of learning mathematics in class A were greater with a mean Rank of 8.63, while in class B with a mean Rank of 8.38. Based on the output test statistics, it is known that the Asymp Sig. (2.talled) value is 0.916 <0.05. The hypothesis is accepted. It can be said that there is a significant difference in results between class A and class B with the effect of learning in the experimental class and the control class.Keywords: Scientific Approach, study, Circle